PENGARUH PENERAPAN KEBIJAKAN TAX AMNESTY, PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA DENPASAR TIMUR - Anggarini, Luh Putu Irma; Yuesti, Anik; Sudiartana, I Made (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2019)
Tax is a compulsory contribution to the state that is owed by an individual or an entity thatis compelling under the law, by not receiving direct compensation and being used for state needsfor the greatest prosperity of the people. This study aims to determine or reexamine the influenceof the application of tax amnesty policies, knowledge of taxation, awareness of taxpayers, andtax sanctions on individual taxpayer compliance at the Pratama Tax Office in East Denpasar.The sampling method in this study used accidental sampling method, with a total sampleof 100 respondents calculated using Slovin formula. The data analysis technique used is multiplelinear regression analysis techniques. The results of this study indicate that the awareness of taxpayersand taxation sanctions has a positive effect on individual taxpayer compliance at the EastDenpasar Tax Service Office which is indicated by the significance value of each variable which is0.001 and 0,000 while the tax amnesty policy and knowledge of taxation do not affect mandatorycompliance personal tax at the Primary Tax Office in East Denpasar, with a significance value ofeach variable which is 0.363 and 0.529.